Research on Detection Technology of 235U Enrichment and Loading Uniformity for Nuclear Fuel Rods - Gu, Mingfei; Huang, Dagui; Yu, Dongbao; Tang, Hui; Zhu, Yongli (Frontiers in Energy Research, 2021)
Abstract: To ensure that fuel rods operate in nuclear reactors safely and reliably, UO2 pellets with different enrichment levels of 235U in same production line are manufactured in batches and divisionally managed. It is prohibited to confuse and misload UO2 pellets with different enrichment levels. At same time, nondestructive test for their enrichment levels and loading uniformity and all UO2 pellets must be nondestructive tested during production. By studying enrichment detection mechanism of UO2 pellets of 235U, the design of integral standard rod was carried out, and single integral standard rod was used to achieve the calibration of enrichment measurement curve, as well as the detection and calibration of abnormal pellets. The comparison test of 235U enrichment between neutron activation method and array multi-probe passive method was carried out in this paper. The test results showed that array multi-probe passive method had higher detection efficiency and equal accuracy.